Video Recording Tasks to Improve Visual Communication Design Students’ Speaking Ability: A Quasi Experimental Study - Wahyuni, Tri; Yuwono, Timbul (Journal of English Language and Education, 2026)
This quasi-experimental study (pretest–posttest control group design) investigates the effectiveness of a Video Recording Task (VRT) in enhancing the speaking ability of second-semester students in a Visual Communication Design (DKV) program. Sixty participants were assigned to control and experimental groups and received six weeks of instruction. While the control group followed traditional speaking activities, the experimental group engaged in structured VRT-based tasks. Pre- and post-test data were collected to assess gains in fluency, accuracy, pronunciation, and vocabulary. The pre-test and post-test results of the experimental group (n = 30) show improvements across all speaking subskills, with fluency increasing from 22.1 to 27.4 (gain = +5.3), accuracy from 23.2 to 27.1 (gain = +3.9), and pronunciation from 24.2 to 27.9 (gain = +3.7). Quantitative results demonstrate a notable improvement in the experimental group, with measurable gains across all four speaking components and a higher overall achievement score compared to the control group. Additionally, participants in the VRT group reported increased confidence and greater engagement in speaking tasks. These findings indicate that integrating video-based activities into ESP instruction significantly supports learners’ oral performance and contributes to technology-enhanced learning practices. The study highlights the pedagogical value of VRT, particularly within creative disciplines such as DKV, and suggests promising implications for future ESP course design.